Translating adventure tourism : from action to relaxation - Mohamed Zain Sulaiman,; Wilson, Rita (Penerbit Universiti Kebangsaan Malaysia, 2018)
Adventure tourism is one of the fastest growing sectors in the tourism industry and, therefore, one of the most important categories marketed and promoted globally. However, the way adventure tourism is represented and perceived differs markedly from one culture to another. Based on how tourism is conceptualised in a particular culture, themes are carefully selected and exploited in promoting ‘adventure’ tourism. The differences in how tourism is conceptualised across cultures pose a key challenge for translators of tourism promotional materials (TPMs), whose role is to produce an effective translation in the target language and culture. Translating TPMs effectively for different cultures often requires changes and adjustments to be made in order to preserve the most vital aspect of TPMs, that is, their functionality. This paper explores the challenges involved in translating English TPMs into Malay and investigates the extent to which the action theme of adventure employed to lure Anglophone tourists is compatible with Malay culture. Three types of textual analysis are carried out: source text analysis, parallel text analysis and target text analysis. The textual analyses are then complemented by findings derived from focus groups. The findings of the study demonstrate how adventure tourism is conceptualised within the notion of action in the Anglo culture, and how this contrasts with the way it is framed within the notion of relaxation in Malay culture. Based on the findings derived from the textual analyses and focus groups, we conclude by proposing potential strategies for the production of functionally adequate translations, which take into consideration the cultural conceptualisation of the target culture.